A Philosophical Expose Towards A ‘God After God’ - Onah, Gregory Ajima; Ogar, Thomas Eneji; Okoi, Ibiang O. (Asosiasi Ahli Filsafat Keilahian Indonesia, 2023)
The escalation of violent incidents in recent times has brought religions to the forefront of world politics, resulting in a shift from their traditional role as conduits of divine revelation to becoming instruments of power and dominance. This phenomenon of kratophany exemplifies the manifestation of violence within religious contexts. The occurrence of violence may be attributed to the foundation of eschatological interpretations within various theological frameworks. The emergence of religious triumphalism and fundamentalism stemming from these theological perspectives has posed a significant danger to both world peace and ecumenical dialogue. The need for peace among faiths has transitioned from being a mere choice to an urgent necessity in contemporary times. The deity that is sought to be understood via the lens of eschatology is a divine being that exists in the future, sometimes referred to as an